SILENCED VOICES: HEALTHCARE NEEDS OF CHILDREN WITH DISABILITIES IN PAKISTAN: Children with disabilities - Asim, Muhammad (Journal of Ayub Medical College Abbottabad, 2022)
The number of children with disabilities is increasing and their healthcare needs are one of the most ignored areas of Pakistan’s health care system. These children face multiple challenges to receiving needed healthcare services that include attitudinal, physical, policy, and programmatic barriers. The commitment to leaving no one behind demands that children with disabilities (CWD) receive inclusive access to the healthcare system. Moreover, the specific healthcare needs of CWD are often overlooked due to lack of research, evidence, and policy measures. It is suggested that an inclusive healthcare system at primary level healthcare facilities should be implemented to improve health outcomes of CWD.